2011
DOI: 10.1111/j.1447-0349.2010.00697.x
|View full text |Cite
|
Sign up to set email alerts
|

Listening to mental health workers' experiences: Factors influencing their work with women who disclose sexual assault

Abstract: Women are overrepresented within mental health service-use statistics, and a disproportionate number of them have experienced sexual assault. While mental health workers are often the first point of contact between these women and the mental health system, within the research to date, women have often reported a negative experience of disclosing sexual assault to these workers. This article presents findings from an exploratory Australian study. The aim of the study was to explore factors that influenced how m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Sexual vulnerability and sexual exploitation, especially for female inpatient consumers, is a further concerning occurrence (Brown, Lubman, & Paxton, 2011;Cole, 2003;Judd, Armstrong, & Kulkarni, 2009;McLindon & Harms, 2011), resulting in some mental health units providing additional safety and security measures for women (Price, 2009). The incidence of sexual side effects from psychotropic medications also has significant implications (Balon, 2006;Basson et al, 2010;Schlachetzki & Langosch, 2008;Schweitzer, Maguire, & Ng, 2009;Werneke, Northey, & Bhugra, 2006) for example, non-adherence and subsequent risk of relapse (Basson et al, 2010;Deegan, 2001;Schweitzer et al, 2009).…”
mentioning
confidence: 96%
“…Sexual vulnerability and sexual exploitation, especially for female inpatient consumers, is a further concerning occurrence (Brown, Lubman, & Paxton, 2011;Cole, 2003;Judd, Armstrong, & Kulkarni, 2009;McLindon & Harms, 2011), resulting in some mental health units providing additional safety and security measures for women (Price, 2009). The incidence of sexual side effects from psychotropic medications also has significant implications (Balon, 2006;Basson et al, 2010;Schlachetzki & Langosch, 2008;Schweitzer, Maguire, & Ng, 2009;Werneke, Northey, & Bhugra, 2006) for example, non-adherence and subsequent risk of relapse (Basson et al, 2010;Deegan, 2001;Schweitzer et al, 2009).…”
mentioning
confidence: 96%
“…Still regarding to competence in the management of the patient disease/illness status domain, study on how mental health workers respond to women who revealed sexual abuse, in the scenario of crisis service, showed that the participants recognized the impact of sexual abuse in long term manifestation of sexual trauma and psychiatric symptoms, highlighting the different responses in physical, cognitive, emotional and spiritual experienced by individuals. However, half of the sample did not feel confident to respond to a situation of sexual abuse (11) . The results demonstrated appropriate competence when analyzing and interpreting the patient's history and the information to develop appropriate diagnoses, but they showed difficulties in meeting the patient's response to lived experiences (6) .…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated appropriate competence when analyzing and interpreting the patient's history and the information to develop appropriate diagnoses, but they showed difficulties in meeting the patient's response to lived experiences (6) . All participants identified knowledge of the services from Center Against Sexual Abuse, as well as other specialized services for sexual abuse in the community; however, the majority of participants indicated that they rarely or never refer to these services, which denotes failure of the competence as the issue goes beyond the scope of nursing practice (11) . Among the reported barriers to working with the issue of sexual abuse, 12 participants recognized the need for containment of anxiety as a challenge, eight reported their lack of experience and/or training, and two male workers identified sex as a barrier, reflecting the cultural competence when they recognize cultural issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is only in the last decade that a solid evidence base has emerged which demonstrates that mental ill-health can be a "symptom of [domestic] abuse" (Humphreys & Thiara, 2003), and highlights the extent to which survivors of domestic and sexual violence often use alcohol, illicit drugs and prescribed medication as a means of coping with the physical and emotional pain of abuse (see, for example, Golding, 1999;Howard, Trevillion & Agnew-Davies, 2010a;Howard et al, 2010b;Humphreys & Reagan, 2005;McLindon & Harms, 2011;Rees et al, 2011). The association between substance use and the perpetration of domestic and sexual violence has also been evidenced (Budd, 2003;Galvani, 2004), and research on perpetration and psychiatric illness is currently underway.…”
Section: Introductionmentioning
confidence: 99%